Analisis Homo Deus Dalam Pandangan Harari serta Fakta Kemajuan Teknologi Di Era Society 5.0 - Mitha Mayestika Kuen; Hafied Cangara; Hasrullah Hasrullah (Institut Agama Islam Negeri Kendari, 2022)
Yuval Noah Harari, a historian from the Hebrew University of Jerusalem, has produced works that have become the subject of discussion in the public sphere. The work is Homo Deus (2015) trying to explain